Frequency of Urinary Tract Infection in Simple Febrile Seizures in Children Aged 6 Months to 5 Years - Mishal, Mina; Mansoor, Khola Binet; Javed, Salik (Indus Journal of Bioscience Research, 2025)
Background: The most common type of convulsion in young children is febrile seizures. Urinary tract infections (UTIs) may be to blame, but they may not be found without proper testing. Objective: To determine the frequency of UTIs in children aged 6 months to 5 years presenting with simple febrile seizures. Methodology: This descriptive cross-sectional study took place over six months, from September 6, 2024 to March 06, 2025, at the Mayo Hospital in Lahore, in the Department of Pediatric Medicine, Unit II. A non-probability consective sampling method was used to include 102 children between the ages of 6 months and 5 years who were having simple febrile seizures. To identify UTI, a urine complete examination (UCE) and a urine culture and sensitivity test were done. We used SPSS version 26.0 to look at the data and chi-square tests for subgroup analysis. A p-value of less than 0.05 was considered statistically significant. Results: There were 102 children, and the average age was 29.45 months with a range of 15.30 months. 56.86% were boys. It took an average of 6.78 ± 3.25 minutes for a seizure to happen, and all the children had fever (mean: 38.85 ± 0.65°C). UTI was found in 15.69% of cases, with Escherichia coli being the most common strain (62.50%). UTI was strongly linked to younger age (6–12 months, p=0.041) and seizures lasting less than 5 minutes (p=0.048). Conclusion: A significant proportion of children with simple febrile seizures had underlying UTIs, highlighting the need for routine urine screening in such cases to prevent complications.